2015
DOI: 10.1007/s00276-015-1445-4
|View full text |Cite
|
Sign up to set email alerts
|

Three superficial veins coursing over the clavicles: a case report

Abstract: We report a unique bilateral combination of multiple variations in the superficial venous system of the neck of a 77-year-old male cadaver. On the right side of the neck, the external jugular vein (EJV) crossed superficial to the lateral third of the clavicle constituting a common trunk with the cephalic vein (CV) that drained into the subclavian vein (SCV). On the left side the EJV descended distally, passed over the anterior surface of the medial third of the clavicle and drained into the SCV. The posterior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 10 publications
1
10
0
1
Order By: Relevance
“…The percentage of each CV type and subtype in all the reported cases is listed in Values represent frequencies and percentages. All the percentages were rounded to the nearest whole number [1,2,3,4,5,6,7,8,9,10,13,14,17,18,19,20,22,25].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The percentage of each CV type and subtype in all the reported cases is listed in Values represent frequencies and percentages. All the percentages were rounded to the nearest whole number [1,2,3,4,5,6,7,8,9,10,13,14,17,18,19,20,22,25].…”
Section: Resultsmentioning
confidence: 99%
“…The unusual courses of the CV beyond the clavicle were found on both sides in some of the cadavers at our university, and one side of the JCV was thicker than the other. However, none of the other papers mentioned this detail, with the exception of Anastasopoulos et al [1,17]. Radiological studies of unusual JCVs focused on one side only, which may explain why the percentage of unusual courses reported on both sides was low.…”
Section: Discussionmentioning
confidence: 96%
“…A supraclavicular course of the cephalic vein was reported in 0.2% of cases [ 5 ]. Anastasopoulos et al [ 6 ] reported in 2% of cases the occurrence of anastomosis of cephalic vein with external juguar vein (EJV) via a communicating branch. Knowledge of these variations is essential to clinicians and surgeons for venous access during emergencies and surgery [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…This vein may be injured during distal clavicle fractures, causing the occurrence of a haematoma [1]. Large hematomas may potentially lead to inflammation, fever, or even infection, thus causing impaired wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…A case of three superficial veins running over the clavicles (i.e. the EJV constituting a common trunk with the CV that drained into the subclavian vein on the right side of the neck, and the EJV descending distally to drain into the subclavian vein and additional posterior external jugular vein descending to drain into the CV on the left side) was described by Anastasopoulos et al [1]. Bergman et al [2] describes variants where the EJV 'may pass over the clavicle and open into the cephalic', 'in some cases it forms an annulus around the clavicle' or 'receives' the CV as a tributary.…”
Section: Discussionmentioning
confidence: 99%